54.9k views
5 votes
10x-2x+12=2(3x+5)+2x

2 Answers

5 votes

Answer:

the answer to 10x-2x+12=2(3x+5)+2x is 2

Explanation:

step 1.

Open the brackets by multiplying the valves in the brackets by 2:

10x-2x+12=6x+10+2x

step 2.

Add or subtract the like-terms : x values.

8x+12=8x+10

step 3.

substitute by bringing like terms together:

12-10=8x-8x

2=0

ans =2

User Vkosyj
by
6.2k points
2 votes

Answer: is this pemdas? if not there are no true solutions

Explanation:

hope i helped

User Nikosd
by
6.5k points